Mikroagresi di Tempat Kerja sebagai Perilaku Verbal: Tinjauan Literatur Sistematis tentang Bentuk Kebahasaan, Konteks, dan Konsekuensi Psikologis - Satria Efandi; Wiwik Indrayeni (Pusat riset dan Inovasi Nasional, 2026)
Workplace microaggressions represent subtle and ambiguous forms of interpersonal mistreatment that are frequently normalized in organizational interactions, yet may generate significant psychological consequences for employees. While research in industrial and organizational psychology has extensively examined related constructs such as workplace incivility and ostracism, the linguistic mechanisms through which microaggressions operate remain underexplored. This study aims to systematically review Indonesian-language journal articles published between 2015 and 2025 that address workplace microaggressions and related phenomena, by conceptualizing microaggressions as speech acts. Using a systematic literature review approach guided by the PRISMA 2020 framework, relevant peer-reviewed articles were identified, screened, and analyzed through thematic synthesis. The review focuses on three main aspects: linguistic forms of microaggressions, contexts in which they emerge, and their psychological consequences in formal organizational settings, including companies and educational institutions. The findings indicate that workplace microaggressions are predominantly realized through indirect and ambiguous communicative practices, such as dismissive remarks, stereotypical humor, and interactional exclusion, often occurring within hierarchical relationships and formal work situations. These communicative acts are consistently associated with negative psychological outcomes, including stress, emotional exhaustion, reduced wellbeing, and withdrawal-related work attitudes. By integrating industrial-organizational psychology with linguistic-pragmatic perspectives, this review highlights language as a central mechanism through which microaggressions produce psychological harm at work. The study contributes a conceptual synthesis that underscores the importance of addressing everyday communicative practices in organizational interventions aimed at fostering psychological safety and employee wellbeing.